Claudia caffi’s critical discussions in her conception of the metapragmatics - latrach, boulerbeh (The Notebooks of the Algerian Poetics Laboratory Journal, 2025)
Since Roman Jakobson worked on the property of reflexivity in the language, which has been termed meta-language. It was then used in all semiotic systems. There was a need to derive concepts that tend to be in the same direction of accountability and legitimization, and it was easy to call the terms of it using the Greek prefix and preposition meta. Metapragmatics appears to be one of the most important of these concepts that attracted the attention of researchers such as Claudia caffi, who edited a chapter explaining this concept in the concise encyclopedia of pragmatics supervised by Jacob Mey. This article aims to present what Claudia wrote, especially since what Claudia caffi concluded from the meanings of metapragmatics, is our need for this concept not only in understanding communicative practices - awareness of self and others - but also in order to talk about changing the world through discourse.